2007
DOI: 10.1016/j.pec.2006.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Patient willingness to take teriparatide

Abstract: Objectives- ] is an effective treatment for osteoporosis administered by daily subcutaneous injection. The objective of this study was to determine how much benefit women expect teriparatide to confer before agreeing to perform daily injections.Methods-We recruited postmenopausal women who had recently undergone bone densitometry and were found to have either a T score less than −2.5 at the hip or spine and/or had a Fracture Index (FI) of ≥ 6. Participants completed an Adaptive Conjoint Analysis questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…Treatment decisions can be further complicated by the cost of medication, a patient's insurance coverage, and ability to pay. Taken together, efficacy [11], side effects [12], cost [13], and convenience [14] are factors that can affect persistence. Two previous studies [8,9] combining education and bone marker response to therapy showed no improvement in persistence with bone marker information.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment decisions can be further complicated by the cost of medication, a patient's insurance coverage, and ability to pay. Taken together, efficacy [11], side effects [12], cost [13], and convenience [14] are factors that can affect persistence. Two previous studies [8,9] combining education and bone marker response to therapy showed no improvement in persistence with bone marker information.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the use of FORTEO® is limited by the requirement for injection and the need for product refrigeration. A patient-friendly alternative to this daily injection could improve patient compliance and, thereby, therapeutic outcome (9,10). Intermittent dosing is also important to the mechanism of PTH's anabolic action.…”
Section: Introductionmentioning
confidence: 99%
“…This peptide hormone is unique in its bone-building effect (1), ability to promote bone strength (2,3), and ability to reduce long-term bone fracture risk (4) relative to bisphosphonates (anti-resorptive agents). Despite these clinical benefits, the use of PTH therapy is limited by practical factors (5,6), with one of the most important being mode of administration. As PTH(1-34) is a peptide hormone, it cannot be given orally and currently can only be administered as a daily subcutaneous injection.…”
Section: Introductionmentioning
confidence: 99%